Oblicz całki Crook:
 x2−4x−7 
a) ∫

dx
 (x2+2x+4)(x+3) 
b∫exsin(ex)dx
29 cze 15:57
Jerzy: b) podstawiasz t = ex i dostajesz: ∫sintdt
29 cze 16:04
Mariusz: (x2+2x+4)−6(x+3)=x2−4x−14 x−1 x2+2x+4:x+3 x2+3x −x+4 −x−3 7 (x−1)(x+3)+7=x2+2x+4 7=(x2+2x+4)−(x−1)(x+3) (x2+2x+4)−6(x+3)+(x2+2x+4)−(x−1)(x+3)=x2−4x−14+7 2(x2+2x+4)−(x+5)(x+3)=x2−4x−7
 2(x2+2x+4)−(x+5)(x+3) x2−4x−7 

dx=∫

dx
 (x2+2x+4)(x+3) (x2+2x+4)(x+3) 
 2 x+1 4 

dx−∫

dx−∫

dx
 x+3 x2+2x+4 (x+1)2+3 
 2 x+1 4 
1 

3 
 

dx−∫

dx−


dx
 x+3 x2+2x+4 3 
 x+1 
1+(

)2
 3 
 
 1 43 3 
=2ln|x+3|−

ln|x2+2x+4|−

arctg(

(x+1))+C
 2 3 3 
29 cze 20:17